Horace´s Odes Book 2. Some Remarks on the New "Green and Yellow" Commentary - Bruno, Nicoletta (Exemplaria Classica, 2019)
StephenHarrison(ed.), Horace: Odes, Book II. Cambridge Greek and Latin Classics. Cambridge: Cambridge University Press, 2017, pp. ix+267, ISBN 978-1-107-60090-4.